How to accurately identify the underserved areas of peri-urban parks? An integrated accessibility indicator. (March 2021) - Zhang, Jinguang; Cheng, Yingyi; Zhao, Bing
Highlights: Travel time, park size, and quality are part of the integrated accessibility index. Peri-urban park quality is calculated by aggregating the attractive properties. An improved Huff 2SFCA model is proposed to calculate the integrated index. The (potentially) underserved communities of peri-urban parks are monitored. Abstract: Due to the shortage of green space in urban built environments, access to peri-urban parks in the suburbs has been a focus of planning practices to meet increasing resident demands for recreational visits to natural settings. However, accurate approaches to evaluating peri-urban park accessibility and monitoring underserved areas are lacking. In this study, we propose an integrated accessibility index for peri-urban parks that is calculated using an improved Huff-2SFCA (two-step floating catchment area) model that considers the tradeoffs between quality, park size, and travel time. We first propose a peri-urban park quality index and then integrate it into an accessibility assessment. Furthermore, we employ a variable catchment to ensure that the larger and high-quality parks correspond to higher travel time thresholds. To demonstrate the practicality of the integrated index, Nanjing, a rapidly urbanizing Chinese city, was selected as a case study. The results demonstrate that (1) the quality of peri-urban parks is unevenly distributed, with high-quality parks primarily being distributed in western urban suburbs and occupying a total area of approximately 5665 ha; (2) approximately 92% of communities can enjoy peri-urban park services, while high-quality parks are more accessible to residents living in urban centers; and (3) 220 residential communities are identified as underserved areas, and 142 communities are identified as potentially underserved areas due to long travel times and the poor quality or small sizes of accessible parks. The integrated accessibility index can be employed to accurately monitor (potentially) underserved areas and assist decision-makers in formulating effective policies and strategies for improving residential access to peri-urban landscapes.